2012
DOI: 10.1521/pedi.2012.26.3.381
|View full text |Cite
|
Sign up to set email alerts
|

Personality Disorders and Dimensions in Pathological Gambling

Abstract: Comorbid DSM-IV Axis II personality disorders appear to be common in pathological gambling (PG) and may contribute to the chronic problems often associated with the disorder. This study sought to examine the relationship between PG, personality disorders, and impulsivity in a sample of pathological gamblers. Personality assessments included the SCID-II, Eysenck Impulsiveness Questionnaire, Tridimensional Personality Questionnaire, and Barratt Impulsiveness Scale. A total of 77 individuals with DSM-IV PG were i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
11
0
8

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 58 publications
2
11
0
8
Order By: Relevance
“…10,9,8,28 These studies are consistent with the highly significant main effect of impulsivity on all three levels of gambling involvement in the present study. This is expected given that until the newly revised DSM-5, pathological gambling was defined as an ‘impulse-control disorder’ in the DSM-IV.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…10,9,8,28 These studies are consistent with the highly significant main effect of impulsivity on all three levels of gambling involvement in the present study. This is expected given that until the newly revised DSM-5, pathological gambling was defined as an ‘impulse-control disorder’ in the DSM-IV.…”
Section: Discussionsupporting
confidence: 92%
“…7, 8, 9 In a review of research related to personality dimensions and pathological gambling, Odlaug et al 10 reported that impulsivity is a key personality dimension of pathological gambling with potentially important treatment implications for pathological gambling. However, research is lacking in general population samples with controls for demographic and ecological factors.…”
Section: Introductionmentioning
confidence: 99%
“…Our data confirmed the impulsive nature of pathological gambling (Odlaug, Schreiber, & Grant, 2012). Indeed, results are significant and show positive correlations among impulsivity, dissociation and affect dysregulation (measured by the first factor of the TAS-20; see Toneatto et al, 2009;Pace et al, 2013;Craparo et al, 2013;Gori et al, 2014).…”
supporting
confidence: 83%
“…Whether it represents disregard for consequences, lack of deliberation, or poor executive control, impulsive behavior has been predominantly considered in terms of negative outcomes such as psychopathology (e.g., Feilhauer & Cima, ; Poythress & Hall, ; Saddichha & Schuetz, ), substance abuse (Kirby & Petry, ; Wiers & Stacy, ), overeating and obesity (Gerlach, Herpertz, & Loeber, ; Hofmann, Friese, & Roefs, ; Komlos, Smith, & Bogin, ), pathological gambling (Odlaug, Schreiber, & Grant, ; Petry, ), impulse buying (Dittmar, ), poor outcomes for smoking cessation (López‐Torrecillas, Perales, Nieto‐Ruiz, & Verdejo‐García, ), inappropriate sexual behavior (Hofmann, Gschwendner, Friese, Wiers, & Schmitt, ), and poor grade point averages (Kirby, Winston, & Santiesteban, ). Conversely, deliberate behavior is associated with positive outcomes.…”
Section: How Have We Looked At Impulsive Behavior?mentioning
confidence: 99%